Effect of the addition of silver nanoparticles on the mechanical properties of an orthodontic adhesive - Marco Sánchez-Tito; Lidia Yileng Tay (Elsevier, 2024)
Objectives: This study evaluated the effects of adding silver nanoparticles on the shear bond strength, microhardness, and surface roughness of orthodontic adhesives. Material and Methods: Fifty upper premolars were randomly allocated to five groups (n = 10). Orthodontic brackets were bonded with silver nanoparticle (AgNP)-modified adhesives (1 %, 0.5 %, 0.1 %, 0.05 %), and conventional adhesive was used as a control. The shear bond strength was recorded using a universal testing machine, and the adhesive remnant index was evaluated using a stereomicroscope. Ten discs of each adhesive were subjected to the microhardness and surface roughness tests. The Vickers microhardness values were measured under a constant load of 100 g for 30 s using a microhardness tester. The samples were analyzed using a surface profilometer, and the arithmetic average roughness was used as the measurement parameter. Data were analyzed using one-way analysis of variance and chi-square tests. A significance level of 5 % was considered significant. Results: AgNP concentration > 0.1 % significantly reduced the shear bond strength (p < 0.05). At higher AgNP concentration, the bonding failure pattern occurred mainly at the bracket-resin interface. The Vickers microhardness increased with increasing concentration, and significant differences were observed between the group with 1 % AgNP and the other groups (p < 0.05). The average roughness values were similar between the groups with AgNP concentrations > 0.1 % (p > 0.05). Conclusion: The incorporation of AgNP into an orthodontic adhesive has the potential to decrease the shear bond strength while increasing the microhardness and surface roughness.